Public Policy for Women: The State, Income Security and Labour Market Issues - Prentice, Susan (Labour / Le Travail, 2010)
The article reviews the book, "Public Policy for Women: The State, Income Security and Labour Market Issues," edited by Marjorie Griffin Cohen and Jane Pulkingham.
Keywords: BOOKS -- Reviews; COHEN, Marjorie Griffin; Canada; EMPLOYMENT policy; Nonfiction; PUBLIC Policy for Women: The State, Income Security & Labour Market Issues (Book); PULKINGHAM, Jane

Working Women in Canada: An Intersectional Approach - Nichols, Leslie; Forrest, Anne; Lippel, Katherine; Premji, Stephanie; Tyyskä, Vappu; Aggarwal, Pramila; Ignagni, Esther; Prentice, Susan; Acker, Sandra; Muzzin, Linda; Knight, Melanie; Gabay, Danielle; et al. (Canadian Scholars/Women's Press, 2019)
In this edited collection, Leslie Nichols weaves together the contributions of accomplished and diverse scholars to offer an expansive and critical analysis of women’s work in Canada. Students will use an intersectional approach to explore issues of gender, class, race, immigrant status, disability, sexual orientation, Indigeneity, age, and ethnicity in relation to employment. Drawing from case studies and extensive research, the text’s eighteen chapters consider Canadian industries across a broad spectrum, including political, academic, sport, sex trade, retail, and entrepreneurial work. Working Women in Canada is a relevant and in-depth look into the past, present, and future of women’s responsibilities and professions in Canada. Undergraduate and graduate students in gender studies, labour studies, and sociology courses will benefit from this thorough and intersectional approach to the study of women’s labour. Features include tables, case studies, a glossary of key terms, and chapter introductions and conclusions to assist with student comprehension encourages further learning by concluding each chapter with discussion questions, a list of additional key readings, and an extensive reference list provides a broad portrait of women’s work in Canada with contributions from over 20 scholars. --Publisher's description